Three Decades of Sunda Pangolin (Manis javanica) Conservation Research: Mapping Indonesia’s Role in the Global Engagement Trends - Novriyanti, Novriyanti; Masy’ud, Burhanuddin; Soekmadi, Rinekso; Buchori, Damayanti (Journal of Multidisciplinary Applied Natural Science, 2026)
Limited scientific attention to the Sunda pangolin (Manis javanica) persists despite being among the most trafficked mammals globally and a key species distributed across Indonesia. This study examines Indonesia’s contribution to global Sunda pangolin research and identifies priority directions to strengthen evidence-based conservation. A combined bibliometric–content analysis approach was applied to 4,474 publications recorded between 1993–2023, from which 130 articles met the topic-specific criteria, and 37 were directly related to Sunda pangolin conservation in Indonesia. Results show that Indonesia contributed only 37 documents (0.83%) to the global pangolin research landscape, with 12 thematic categories dominated by trade and crime studies, while ecological and policy-oriented research remained critically underrepresented. Research on Sunda pangolins was also largely driven by international authors from non-habitat countries, indicating a lack of local leadership and collaboration gaps. These findings highlight a strategic need to increase locally led and multidisciplinary research, expand Indonesia’s role as a key habitat country, and establish collaborative research agendas that align ecological knowledge, conservation policy, and wildlife crime mitigation.